Effect of laser spot diameter on the processing and microstructural properties of AlCoCrFeNi2.1 eutectic high-entropy alloy formed by selective laser melting - Gang Wang; Xiangyu Xu; Ren Yuan; Xuteng Lv (Journal of Materials Research and Technology)
AlCoCrFeNi2.1 eutectic high-entropy alloy (EHEA) was fabricated using the selective laser melting (SLM) method. Optimal printing parameters were determined for laser spot diameters of 50 μm, 70 μm, and 85 μm. This study investigates the formation defects, microstructural variations, and high-temperature mechanical behavior of EHEA under different spot diameters. The results show that increasing the spot diameter reduces the occurrence of lack of fusion, cracking, and spatter, thereby significantly expanding the process window. At a spot diameter of 85 μm, the sample achieved a maximum relative density of 99.8 %. Changes in melt pool energy distribution caused by different spot sizes influenced the microstructure in multiple ways. As the spot diameter increased, the fraction of face-centered cubic (FCC) phases decreased, grain size increased, and recrystallization was enhanced, leading to variations in grain boundary characteristics, Kernel Average Misorientation (KAM) values, and texture. Benefiting from reduced defects and higher density, the 85 μm sample exhibited the highest average tensile strength of 1564 MPa and an elongation of 13.1 %. Furthermore, its tensile strength at 300 °C exceeded that at room temperature. This study offers insight into the variability of optimal Volumetric Energy Density (VED) values reported in the literature and provides useful guidance for processing AlCoCrFeNi2.1 EHEA, while the mechanical performance results establish a basis for its potential high-temperature applications.